RESEARCH OF THE ECO-FLORISTIC DATA INTO THE CONTRIBUTION OF GROUPS TO HALOPHYTE, HAMMAM BOUGHRARA AREA WEST ALGERIA - Benabdelmoumene, Fatna; Benabadji, Noury; Benchenafi, Souhila; Benmensour, Djamel (European Scientific Journal, ESJ, 2014)
This article presents the results of a phytosociological study bearing on the floristic diversity of a few stations in the North West of Algeria. The latter is carried out on the basis of statistical analysis of 90 identifies a particular attention is paid to climatic and soil conditions.The results show that the osmotic pressure of the soil solution where a specific ion toxicity can lead to the formation of particular landscapes.